THE USE OF KUNG FU PANDA FILM SERIALS TO ENHANCE STUDENTSâ ABILITY IN WRITING NARRATIVE TEXT - Nugroho, Tsalits Muhammad (ELT Forum: Journal of English Language Teaching, 2014)
This final project is about the use of films as learning media to improve the writing skill of narrative text at eleventh grade students of SMA N 1 Banjarnegara in the academic year of 2013/2014. This study aimed at knowing the difficulties faced by the students and the extent of the Kung Fu Panda Film Serials implementation on the improvement of their writing skill in creating narrative text. To achieve the objectives, an action research was designed and carried out through preliminary observation, formative observation, and post observation. The subject of this research was 34 students of class XII social 2 of SMA N 1 Banjarnegara. I used writing tests, observation checklist, and questionnaire as the instruments for collecting the data. There were six meetings in this research. First meeting was used for conducting pre-test, second, third and fourth meeting were used to conduct cycle 1 and formative test, and fifth and sixth meeting were used to conduct cycle 2 and post-test. The results of the study, after analyzed and described qualitatively, showed a significant improvement of the studentsâ achievement. The studentsâ writing skill improved in all writing aspects: grammar, vocabulary, mechanic, relevance, and fluency. The result of the observation sheet showed that after learning narrative texts using Kung Fu Panda Film Serials, the students became more cooperative, active, and the class become more joyful. The analysis of the questionnaire showed that the students gave positive responses towards the use of Kung Fu Panda Film Serials as media in their learning.